Prediktor Perilaku Merokok Pada Pengguna Rokok Elektrik Ditinjau Dari Health Belief Model: Sebuah Studi Literatur - Wardah Wuri Aisyati; Kesuma Dewi , Triana (CV RIFAINSTITUT, 2023)
The development of the times has influenced changes in the pattern of life in society. One of them is smoking behavior which is no longer considered a taboo by some people. In Indonesia, e-cigarette users continue to increase every year. E-cigarette enthusiasts are not only men, but many women are also interested in consuming e-cigarettes. Even some of them are new users and decide to become active smokers. The prevalence of female e-cigarette users in Indonesia in 2018 reached 2.7% of users. One model and theory of healthy behavior that can describe an individual's belief in a behavior, especially in the context of this study, namely smoking behavior in women who use e-cigarettes is the health belief model (HBM). Therefore, the author would like to conduct a narrative review of the literature before conducting further research.